Peran Budaya Pondok Pesantren dalam Membentuk Karakter Santri - Fitriani (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2022)
The purpose of this study was to determine the role of Islamic boarding school culture in shaping the character of students and to find out what factors were the supporters and obstacles in shaping the character of students. This research was made using a qualitative approach with a descriptive qualitative research type. The informants in this study were the administrator, the head of the madrasa, ustadzah/ustadz, and several students of the Al-Kautsar Islamic boarding school. In collecting research data using observation, interviews, and documentation techniques which are then analyzed by presenting data, data reduction, and drawing conclusions that will be the results of the research, to test the validity of a research data using triangulation techniques. This research was conducted at the Al-Kautsar Ranggo Islamic Boarding School, Pajo District, Dompu Regency, West Nusa Tenggara Province. From the results of the study, it was found that the role played by the Al-Kautsar Islamic Boarding School in shaping the character of the students was the existence of a deep sense of sincerity that the ustadz/ustadz had in providing subject matter, the placement of teaching staff depended on the competencies possessed, and with good cooperation between educators. and administrators in every activity. Supporting factors in the application of students are the support from the community around the Al-Kautsar Islamic boarding school, the presence of experienced ustadz/ustadz, the strong will of students to study religious knowledge, the values ​​of togetherness between the clerics, administrators, and students, and a sufficient number of teachers or mentors will be able to replace the presence of parents while at the boarding school because they act as models and as therapists. While the inhibiting factor in shaping the character of students is the pattern of student behavior which is sometimes difficult to regulate, the lack of ukhwah Islamiyah.